Analysis of Used Clothing Traders' Income in Manado City - Angkow, Stephany A. P.; B. Kalangi, Josep; Y. L. Tumangkeng, Steeva (PT FORMOSA CENDEKIA GLOBAL, 2024)
The used clothing trade is quite popular in Manado City. The lifestyle of people who want clothes that have good quality and well-known brands but at low prices has created the phenomenon of buying and selling used clothes in the city of Manado. So currently many people are interested in selling used clothes in search of income and thus competition between used clothes sellers is also getting tighter. In this research the author used primary data. Primary data was obtained using data collection techniques in the form of: interviews, opinion polls, distributing questionnaires, observation and focused discussions. This research shows that the average level of income and profits for used clothing traders in Manado City is quite large and stable. And the ratio between income and total costs incurred by traders is >1 so that the business experiences a profit.